Identification of Potential Tourist Attractions in Puspamukti Tourism Village, Cigalontang District, Tasikmalaya Regency - Mohamad Mardatillah; Siti Fadjarajani; Cahya Darmawan (WINDRADI: Jurnal Pengabdian Masyarakat, 2024)
Natural resources in rural areas of Tasikmalaya Regency have very good potential. Tourism potential in Tasikmalaya Regency is very abundant and needs to be developed. Identification of potential tourist attractions needs to be done for the development of tourist attractions. Tourism villages are one solution to add or develop every potential owned by a village. Tourist attractions are part of the objects or activities offered by a tourist village to attract tourists. Therefore, it is necessary to identify the potential attractions in the Puspamukti tourist village in order to provide additional information for readers. This research method uses a qualitative method with field observation and interview data collection techniques. From the results of this study, there are eight potential tourist attractions in the Puspamukti tourist village. The potential tourist attractions are cirimbing, mentari sakti, guess manis, angleng darma, penyerangabbta kasongket, coffee processing, black sticky rice agrotourism center point, and pine forest camping ground. The purpose of this study is to identify the potential tourist attractions in the Puspaukti Tourist Village so that it can provide information and also increase the promotion of the Puspaukti Tourist Village.